Formulasi Proses Belajar Mengajar Akuntansi Multiparadigma dengan Pendekatan Hypnoteaching - Espa, Vitriyan (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2014)
Formulation of Accounting Multiparadigm Teaching and Learning with Hypnoteaching. Teaching and learning approach with a particular paradigm has led to the formation of student character who would affect his behavior in the community. Positivism, Interpretisvism, Criticism, and Postmodernism are paradigms that are used in the multiparadigm learning approach. This study used a qualitative method by applying hypnomethodology tolecturers and students. Hipnoteaching is believed to be the most effective teaching method in the teaching and learning process, in this case specifically aimed at learning the science of accounting. Hypnoteaching was formulated in a way that faith is rested with permission from God Almighty, and that whatever is desired by humanwith wholehearted efforts could be realized. Kata kunci: Multiparadigma, hipnoteaching, akuntansi